To Placate or Provoke? A Critical Review of the Disciplines Approach to History Curriculum - Cutrara, Samantha (Journal of the Canadian Association for Curriculum Studies, 2010)
Although there are many models that attempt to take Canadian history curriculum in more critical, thought-provoking directions, most notably the disciplinary cognitive citizenship’ approach spearheaded in Canada by Peter Seixas, these reforms are so typical of the transaction orientation that there is no room for what I think history can and should do: transform. Canadian history curriculum needs to take seriously the homogenizing ethic of today’s neoliberal politics by acknowledging the power and privilege imbedded within historical narratives. By structuring history education so that there is no place to think of the Canadian historical narrative outside a rational and depolitical framework, under the guise of a provocative curriculum, an approach like the disciplinary cognitive citizenship approach seeks to placate students in a neoliberal understanding of self rather than prepare them for the diversity of 21st century Canada.